Synthesis, Characterisation and Reactivity of Copper(I) Amide Complexes and Studies on Their Role in the Modified Ullmann Amination Reaction. Issue 19 (18th March 2015) - Sung, Simon; Braddock, D. Christopher; Armstrong, Alan; Brennan, Colin; Sale, David; White, Andrew J. P.; Davies, Robert P.
Abstract: A series of copper(I) alkylamide complexes have been synthesised; copper(I) dicyclohexylamide (1 ), copper(I) 2, 2, 6, 6‐tetramethylpiperidide (2 ), copper(I) pyrrolidide (3 ), copper(I) piperidide (4 ), and copper(I) benzylamide (5 ). Their solid‐state structures and structures in [D6 ]benzene solution are characterised, with the aggregation state in solution determined by a combination of DOSY NMR spectroscopy and DFT calculations. Complexes1, 2 and4 are shown to exist as tetramers in the solid state by X‐ray crystallography. In [D6 ]benzene solution, complexes1, 2 and5 were found by using 1 H DOSY NMR to exist in rapid equilibrium between aggregates with average aggregation numbers of 2.5, 2.4 and 3.3, respectively, at 0.05 M concentration. Conversely, distinct trimeric, tetrameric and pentameric forms of3 and4 were distinguishable by one‐dimensional 1 H and 1 H DOSY NMR spectroscopy. Complexes3 –5 are found to react stoichiometrically with iodobenzene, in the presence or absence of 1, 10‐phenanthroline as an ancillary ligand, to give arylamine products indicative of their role as potential intermediates in the modified Ullmann reaction. The role of phenanthroline has also been explored both in the stoichiometric reaction and in the catalytic Ullmann protocol. Abstract : I‐Cu reacting! New insights into the copper iodide catalysed Ullmann amination reaction involving dialkylamines have been obtained by way of preparation and detailed structural characterisation of a series of copper(I) amide complexes, both in the absence and presence of 1, 10‐phenanthroline (phen).